The validity and reliability of writing attitude scale for EFL learners in the Indonesian context - Setyowati, Lestari; Karmina, Sari; Sukmawan, Sony; Shafie, Latisha Asmaak (Studies in English Language and Education, 2023)
Having a positive attitude in writing is very important since the positive attitude will make the students approach writing in a good way and will enable them to finish the writing task well. Thus, an appropriate instrument to measure the writing attitude is needed. Yet, scarce research is dedicated to investigating the validity and reliability of the writing attitude scale. This research is intended to investigate the validity and reliability of the writing attitude scale adapted from Podsen (1997) which was originally developed from the Daly-Miller Writing Apprehension Test (Daly Miler, 1975b). The design of this study was an observational, non-experimental study with a cross-sectional design, in which the researchers focused on analyzing Podsens (1997) Writing Attitude Scale (WAS). The population of the study was 96 students who took the Essay Writing course in the English Department, at a public university in East Java. The data were in the form of numbers on an ordinal scale. The researchers used the Content Validity Ratio (CVR) to analyze the validity and Cronbach alpha to check the inter-item correlation coefficient in SPSS 25. The result of the study shows that the CVR analysis was 1, and all items in the questionnaire were valid (p=.000.000) as shown in the Pearson product-moment analysis. Secondly, the internal consistency of Podsens (1997) Writing Attitude Scale was high (r.877). This implies that the instrument is applicable because it possesses validity and is highly reliable in measuring students writing attitudes.